Molecular Mechanisms of Memory Consolidation That Operate During Sleep - Reyes-Resina, Irene; Samer, Sebastian; Kreutz, Michael R.; Oelschlegel, Anja M. (Frontiers in Molecular Neuroscience, 2021)
The role of sleep for brain function has been in the focus of interest since many years. It is nowadays firmly established that sleep and the corresponding brain activity is of central importance for molecular memory consolidation. Less clear are the underlying mechanisms and their specific contribution to the formation of long-term memory. In this review we summarize the current knowledge of such mechanisms and we discuss the several unknowns that hinder a deeper appreciation of how molecular memory consolidation during sleep impact synaptic function and engram formation.